2008
DOI: 10.1016/j.virol.2008.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Stacking interactions of W271 and H275 of SeMV serine protease with W43 of natively unfolded VPg confer catalytic activity to protease

Abstract: N-terminal serine protease domain of Sesbania mosaic virus polyprotein, requires fused VPg for its activity. W43 of VPg mediates aromatic stacking interactions (characterized by 230 nm positive CD peak) with protease. A stretch of aromatic residues (F269, W271, Y315, and Y319) exposed in the protease domain were mutated to identify the interacting partner of W43. W271A Protease-VPg mutant showed absence of cleavage activity both in vivo and in trans, with concomitant loss of the 230 nm CD peak. F269A Protease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The structure and the assembly of the virus have been described earlier [18], [19], [20], [21]. The Pro, RdRp, VPg and the P8 domains have been functionally characterised and the latter two are shown to be natively unfolded [22], [23], [24], [25]. In an earlier study SeMV MP was shown to interact with SeMV CP via the N terminal domain [26].…”
Section: Introductionmentioning
confidence: 99%
“…The structure and the assembly of the virus have been described earlier [18], [19], [20], [21]. The Pro, RdRp, VPg and the P8 domains have been functionally characterised and the latter two are shown to be natively unfolded [22], [23], [24], [25]. In an earlier study SeMV MP was shown to interact with SeMV CP via the N terminal domain [26].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of infectivity upon mutation of E132 suggests that cleavage at this site by the protease domain is important for release of NΔ132Pro-VPg from membrane. This NΔ132Pro-VPg might perform proteolytic functions in trans as shown earlier [11], [15], [26] and these trans functions also are crucial for replication/CP accumulation. In Potato leafroll virus (genus Polerovirus ), a similar cleavage site was identified and it was proposed that release of protease domain from the membrane may have a regulatory role [36].…”
Section: Discussionmentioning
confidence: 66%
“…Earlier studies have shown that mutation of cleavage site E325 in the ΔN70 polyprotein 2a results in accumulation of ΔN70Protease-VPg, which is an active form of the protease [11], [15]. Further in vitro studies also showed ΔN70Protease-VPg could act in trans and could cleave the polyprotein 2a at E325 and E402 positions [11], [15], [26]. A significant accumulation of full length Pro-VPg was also observed in membrane fractions of SeMV icDNA infiltrated leaf samples (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…262,[273][274][275][276] The computational analysis showed that functionally important disordered VPg representative of viral diversity includes four members of the Caliciviridae family, six potyviruses and six sobemoviruses. 276 The disordered VPg components associated with the regulation of enzymatic activity in different viruses 273,277 in addition to performing specific regulation and transportation of viral RNA from one cell to another. 278…”
Section: Intrinsic Disorders In Viral Genome-linked Proteinsmentioning
confidence: 99%